Analytical Solution of FSO-Mimo System Peformance Using DWDM Optical Communication - et. al., J. Shanthini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now days, in optical communication network challenge requirement are a high quality factor, good performance in terms of parameters like Bit Error Rate (BER), Eye Diagram. An objective of this paper, to analysis the attenuation value for a haze and normal weather condition respectively, and analysis, performance result of the different optical system has been compared in terms of received signal strength and quality factor of the different haze atmosphere. In this proposed paper used FSO with SISO and FSO-MIMO system for measuring the Q-factor and BER for various data link in different atmosphere. Finally, simulation result shows that the improved FSO link over the existing technique in terms of both the parameter signal power strength and quality factor.